Mathematical model of a hydrogen solid oxide fuel cell and its software implementation - I. M. Gorjunov; A. A. Nikitin; A. A. Loskutnikov; N. E. Ivanov (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение)
An analysis of the existing mathematical models allowing thermogasdynamic calculations of gas turbine engines of various thermogasdynamic cycles is carried out. It was found that most models do not allow calculation with solid oxide fuel cells or in case methane is used as fuel, with subsequent production of hydrogen as a result of steam-water conversion. Therefore, a mathematical model of a solid oxide fuel cell has been developed that considers internal electrochemical reactions followed by the determination of the main electrochemical parameters with hydrogen used as fuel. Computational studies have been carried out on the basis of the developed mathematical model, and the results of evaluating its adequacy are presented that demonstrate a high correlation with the experimental data, which confirms the accuracy of the description of work processes and the applicability of the developed mathematical model of a solid oxide fuel cell. The developed mathematical model is implemented as a module in the DVIGwT software package. The application of the developed mathematical model of a solid oxide fuel cell and its software implementation will allow performing thermogasodynamic calculations of advanced schemes of gas turbine engines, including solid oxide fuel cells, and will also reduce time costs and technical risks when performing a large complex of design calculations.